Conjunctival myxoma: a case report. Issue 9 (September 1984) - Pe'er, J; Ilsar, M; Hidayat, A
Abstract : A rare case of conjunctival myxoma in an 18-year-old female is reported. Clinically it presented as a painless mass located in the nasal bulbar conjunctiva. It was composed of spindle and stellate shaped cells in a loose mucoid stroma. Some of the cells had intracytoplasmic vacuoles consistent with dilated rough endoplasmic reticulum and/or intranuclear vacuoles of nuclear membrane invaginations. Mast cells were also seen in the stroma. No recurrence has been reported eight months postoperatively.